2021
DOI: 10.1101/2021.09.16.460607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Helical metaphase chromatid coiling is conserved

Abstract: The higher-order metaphase chromosome organization has been under controversial discussion already for 140 years. Classical light and electron microscopy proposed chromatids to be composed of helically organized chromatin fibers, so-called chromonemata. More recently also non-helical models were suggested. We studied the chromosome organization in barley by interdisciplinary cutting-edge approaches, such as chromosome sorting, chromosome conformation capture, oligonucleotide-fluorescence in situ hybridization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…Thus, we reasoned that imaging the DNA should be the most direct method to interrogate the native structure. We imaged mitotic chromosomes in metaphase-arrested HeLa cells using 3D-SIM with the cyanine dye, YOYO-1, which has a high affinity for DNA and bright fluorescence with a low background (Figure A). , We note that it is believed that the metaphase chromosome higher-order structure is quite similar among mammalian cells, , and so these results from HeLa cells should be applicable to mammalian cells in general. These images revealed easily appreciable granular domains (that we call compact granules (CGs)) more or less homogeneously distributed throughout each chromosome (Figure A and Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we reasoned that imaging the DNA should be the most direct method to interrogate the native structure. We imaged mitotic chromosomes in metaphase-arrested HeLa cells using 3D-SIM with the cyanine dye, YOYO-1, which has a high affinity for DNA and bright fluorescence with a low background (Figure A). , We note that it is believed that the metaphase chromosome higher-order structure is quite similar among mammalian cells, , and so these results from HeLa cells should be applicable to mammalian cells in general. These images revealed easily appreciable granular domains (that we call compact granules (CGs)) more or less homogeneously distributed throughout each chromosome (Figure A and Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…A complex study of the higherorder 3D structure of both metaphase and interphase chromosomes was presented by H. Šimková (IEB). By a combination of Hi-C and chromosome painting techniques, she demonstrated that sister chromatids of barley metaphase chromosomes have a helical structure, where one turn contains 20 -38 Mbp chromatin-packed DNA, depending on the position on the chromosome arm (Kubalová et al 2021a). Microscopy is a classical technique to study cell nuclei and chromosomes.…”
Section: Nuclear Biology Research Benefits From the Technological Adv...mentioning
confidence: 99%
“…For these reasons, Oligopaints are widely applied to assess the organization of TADs, A/B compartments and other chromatin domains in different model organisms ( Boettiger and Murphy, 2020 ; Hu and Wang, 2021 ). Moreover, this type of FISH-probe is used to address questions of chromatin fiber organization within highly compacted metaphase chromosomes ( Kubalová et al, 2021 ). In further sections, we briefly review major insights from FISH-imaging, which together with 3C-based methods aided pieces to the puzzle of spatial organization of chromatin domains in human, mouse, Drosophila and other model genomes.…”
Section: Fish-probes For Chromatin Domain Visualizationmentioning
confidence: 99%